THE INFLUENCE OF INDUSTRY ON THE KNOWLEDGE SOCIAL ECONOMY OF ENTREPRENEUR IN KARANGANYAR VILLAGE, WERU DISTRICT, SUKOHARJO REGENCY, 2020 - Saputra, Ridho Nur Dwi; Rahman, MS Khabibur; Wijayanti, Ary (Journal of Geography Science and Education, 2020)
This study aims to determine the distribution map of tofu industry in Karanganyar Village, Weru District, Sukoharjo Regency, to know the marketing coverage of the tofu industry in Karanganyar Village, Weru District, Sukoharjo Regency, to determine the socio-economic characteristics of tofu entrepreneurs in Karanganyar Village, Weru District, Sukoharjo Regency. This research used a qualitative descriptive. Data collection techniques used field observations, questionnaires and documentation. The data analysis technique used data reduction, data presentation, drawing conclusions / verification. The results of this study are the distribution of tofu industry in Karanganyar Village, Weru District, Sukoharjo Regency, there are 44 industries spread  in several hamlets. The marketing coverage of the tofu industry in Karanganyar Village covered the area throughout Soloraya and Yogyakarta such as Sukoharjo, Klaten, Wonogiri, Karanganyar, and Gunungkidul. The socio-economic characteristics of entrepreneurs are the majority of men, aged 15-64 years, are married, average education level is elementary school, length of business is 10-30 years, working hours are 7-10 hours per day, income level is more than IDR 2,000,000 and family dependents of less than 3 people. The socio-economic characteristics of the workers are the majority of men, aged 15-64 years, married status, average education level of elementary school, working more than 10 years, working hours 7-10 hours per day, income level of IDR 1,000,000 - IDR 2,000,000 and family dependents of less than 3 people.